Extended Reality in Agricultural Education: A Framework for Implementation - Daniël Haarhoff Naudé; Benjamin Stephanus Botha; Lizemari Hugo; Henry Jordaan; Willem Abraham Lombard (Education Sciences)
Agriculture 4.0 technologies have the potential to revolutionise both agricultural production and the way we educate the next generation of agricultural scientists. As many students enrolling in agricultural science education lack an agricultural background, it is difficult for them to grasp complex agricultural principles in an educational setting. Students without experience are thus at a disadvantage compared to others with prior knowledge. Technologies such as extended reality (XR) can be used as a tool to bridge the gap between theory and practice. With its ability to replicate real-world agricultural production principles within a classroom, XR can provide students with the necessary agricultural experience required within the industry. However, existing literature lacks comprehensive frameworks to guide educators on the implementation of this technology, which could lead to unsuccessful implementation. To ensure the successful implementation of XR in agricultural science education in higher education settings and to bridge the theory-practice gap, this article used the best-fit synthesis to develop a comprehensive framework from the existing literature. This framework can guide educators on the implementation of XR in higher education settings. The findings suggest that agriculture determinants, curriculum development, and facilitating conditions are three important concepts to consider for successful implementation. This XR-AgriEdu framework can be used by educators in agricultural science education to successfully implement XR.